Explicit Error Estimates for Courant, Crouzeix-Raviart and Raviart-Thomas Finite Element Methods (Journal of Computational Mathematics, 2018)
The elementary analysis of this paper presents explicit expressions of the constants in the a priori error estimates for the lowest-order Courant, Crouzeix-Raviart nonconforming and Raviart-Thomas mixed finite element methods in the Poisson model problem. The three constants and their dependences on some maximal angle in the triangulation are indeed all comparable and allow accurate a priori error control.
Keywords: Error estimates; Conforming; Nonconforming; Mixed; Finite element method.